Doping of Carbon Materials for Metal‐Free Electrocatalysis. Issue 7 (19th December 2018) - Hu, Chuangang; Dai, Liming
Abstract: Carbon atoms in the graphitic carbon skeleton can be replaced by heteroatoms with different electronegative from that of the carbon atom (i.e., heteroatom doping) to modulate the charge distribution over the carbon network. The charge modulation can be achieved via direct charge transfer with an electron acceptor/donor (i.e., charge transfer doping) or through introduction of defects (i.e., defective doping). Various doping strategies, including heteroatom doping, charge‐transfer doping, and defective doping, have now been devised for modulating the charge distribution of numerous graphite carbon materials to impart new properties to carbon materials. Consequently, carbon nanomaterials with defined doping have recently become prominent members in the carbon family, promising for a variety of applications, including catalysis, energy conversion and storage, environmental remediation, and important chemical production and industrial processes. The purpose of this review is to present an overview on the doping of carbon materials for metal‐free electrocatalysis, especially the development of doping strategies and doping‐induced structure and property changes for potential catalytic applications. Current challenges and future perspectives in the doped carbon‐based metal‐free catalyst field are also discussed. Abstract : Various doping strategies, including heteroatom‐doping, charge‐transfer doping, and defective‐doping, have been devised for modulating the charge distribution of carbon materials to impart new properties. Doped nanocarbons are promising materials for various applications, including catalysis, energy conversion and storage, environmental remediation, and chemical production and industrial processes. A concise, but comprehensive and critical, overview of this field is presented.